Experience of distributing 499 burn casualties of the June 28, 2015 Formosa Color Dust Explosion in Taiwan. Issue 3 (May 2017) - Wang, Tsung-Hsi; Jhao, Wei-Siang; Yeh, Yu-Hua; Pu, Christy
Highlights: Lack of immediate beds is always a problem during mass burn casualty events. We described the experience of distributing 499 burn victims. Satisfactory patient outcomes can be achieved by lower-level hospitals. Secondary transfers are not associated with patient outcome. Abstract: Objective: To describe the experience of distributing 499 burn casualties of an unexpected event and determine whether patient transfer is associated with patient outcomes measured 2 weeks after the incident. Methods: All 499 patients injured in the event were included. For the 138 patients transferred to other hospitals after primary distribution, we evaluated whether the transfers were associated with patient severity. Furthermore, we used multinomial logistic regression to investigate the association of patient transfer with patient outcomes after controlling for age, gender, total burn surface area (TBSA), final hospital level, wound infection, and patient pneumonia. Results: We determined that on-site triage differed significantly from hospital triage (p < 0.001). Furthermore, the secondary distribution enabled the transfer of a high number of patients to medical centers based on the availability of beds; however, such transfers were not associated with patient outcomes (p > 0.05). Factors associated with patient outcomes were wound infection and TBSA (p < 0.001). Conclusions: In case of inadequate burn centers, satisfactory patient outcomes can be achieved by the immediate treatment of patients, despite the treating hospitals being lower-level hospitals. Regardless of the hospital level, immediate treatment of burn patients is crucial to reducing mortality.